Evaluación de los factores que afectan la calidad higiénico sanitaria de la longaniza artesanal comercializada en el cantón Bolívar - López Basurto, Viviana Vanessa (2019)
The objective of this research work was to determine the factors that affect the hygienic-sanitary quality of artisanal sausage elaborated and sold in Bolivar Canton. Information was collected from five sites for the production of sausage and five for sale Bolívar canton, through an observation form, based on criteria indicated by the NTE INEN 2687 standard and the Good Handling Practices according to the ARCSA. Samples from the 10 sites, taken in two moments, were analyzed microbiologically. The parameters analyzed were: Salmonella and Escherichia Coli according to NTC 1325. It was determined that there is a high rate of non-compliance (87.5%) in processing and sales (100%), this is due to sources of contamination such as: places that are exposed to some kind of pollution; they do not have walls and floors constructed of materials that allow adequate cleaning and sanitation, lack of use of necessary clothing and cross contamination that occurs during the sale. In the microbiological evaluation a general probability of contamination is established for E. Coli 60% and salmonella 80%. The basic manuals for making and selling sausage were disseminated.